2018
DOI: 10.32468/espe.8601
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Earnings and Academic Expectations of Tertiary Education in Colombia

Abstract: We analysed the academic expectations and earning expectations of a nationally representative sample of Colombian students who were finishing their upper-secondary education (high school) and considering three potential scenarios: whether to finish their studies, enrol in a vocational career, or pursue a college degree. We found that these students' earning expectations are correlated with local labour market wages. However, they expect earnings as university graduates that are significantly above the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Second, we found direct (for family income) and indirect (for parental education and family income) influences of family on the formation of salary expectations, which is also consistent with the results of previous studies (e.g., Androushchak & Natkhov, 2010; Botelho & Pinto, 2004; Brunello et al., 2004; Gamboa & Rodríguez Lesmes, 2014; Prakhov, 2017; Smith & Powell, 1990; Webbink & Hartog, 2004). It was shown that maternal education can influence salary expectations indirectly, that is, through USE scores.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Second, we found direct (for family income) and indirect (for parental education and family income) influences of family on the formation of salary expectations, which is also consistent with the results of previous studies (e.g., Androushchak & Natkhov, 2010; Botelho & Pinto, 2004; Brunello et al., 2004; Gamboa & Rodríguez Lesmes, 2014; Prakhov, 2017; Smith & Powell, 1990; Webbink & Hartog, 2004). It was shown that maternal education can influence salary expectations indirectly, that is, through USE scores.…”
Section: Discussionsupporting
confidence: 91%
“…Family income is another factor that can have a positive effect on students’ salary expectations (Androushchak & Natkhov, 2010; Botelho & Pinto, 2004; Gamboa & Rodríguez Lesmes, 2014; Smith & Powell, 1990; Webbink & Hartog, 2004), both through USE results and directly (Prakhov, 2017): first, students can focus on their parental income, and expect to receive no less after they graduate from university. Thus, family income can serve as a guideline or focal point for students.…”
Section: The Analytical Framework Of the Study: The Model Of Salary Expectationsmentioning
confidence: 99%
See 1 more Smart Citation